Analisis Kepailitan Perusahaan Yang Tercatat di BEI Sub Sektor Telekomunikasi - Muhammad Nur Abdi; Agusdiwana Suarni; Arvina Arham (Jurnal Multidisiplin Madani, 2022)
The purpose of this study is to analyze the bankruptcy of companies in the telecommunication sub-sector listed on the IDX for the 2016-2019 period using the Altman ZScore. Quantitative research methods use secondary information. Sources of information from the company's financial statements PT Telekomunikasi Tbk, PT XL Axiata Tbk, & PT Indosat Tbk. Based on the Altman ZScore, five types of ratios are used, namely working capital/complete assets, retained earnings/absolute assets, earnings before interest & taxes/all out assets, market value of equity/book value of debt, & sales/all out assets. With the formula ZScore = 1.2X1 + 1.4X2 + 3.3X3 + 0.6X4 + 0.1X5. The results stated that PT Telekomunikasi Indonesia Tbk was in good health from 2016 to 2019. PTXLAxiataTbk and PTIndosatTbk 2016-2019 were in a bankrupt or unhealthy condition.